Religious Leader’s Views Living Hadith Practices in Malaysia - Norsaleha Mohd. Salleh; Mohd Farid Ravi Abdullah; Abur Hamidi Usman; Rosni Wazir; Abu Zaki Ismail; Nurul Ain Burhanuddin (Jurnal Living Hadis, 2020)
Living Hadith is a cultural phenomenon practiced by a particular society and based on the hadith of the Prophet pbuh. It is a behavioral pattern resulted by the interaction of Muslims with the hadith. This study examines the extent to which the sunnah is practiced by the Muslim community in Malaysia, in addition to explaining the concept of “practicing the sunnah” in the perspective of Living Hadith as a research genre. In doing so, I interview five respondentsincluding muftis, academics, and religious figures who are active in the community. The findings show that the Muslim community barely knows the text of the hadith. They simply practice the content or what they believe to be the teaching of the prophetic hadith, encapsulating in their custom. Performing this, they have the rooted tendency to live in line with the religious and moral demands of Rasulullah pbuh. However, the community also needs to be ‘taught’ to see this practice as a sort of encouragement to perform good deeds. This practice nevertheless is not at the same obligatory level as the command to perform five daily prayers and Ramadan fasting. In other words, the Malaysian society sees the ‘living hadith’ as merely the practice of sunnah that is thus still related to the Prophet pbuh.